Implementing internet-delivered cognitive behavioural therapy for patients with cardiovascular disease and psychological distress: a scoping review. (June 2019) - Neher, Margit; Nygårdh, Annette; Nilsen, Per; Broström, Anders; Johansson, Peter
Background: Comorbid psychological distress (i.e. insomnia and depression) is experienced by 20–40% of patients with cardiovascular disease. This has a considerable impact on their health and quality of life, leading to frequent re-hospitalisations, higher healthcare costs and a shorter life expectancy. Internet-based cognitive behavioural therapy shows great potential for treating psychological distress in cardiovascular disease. Effective and feasible treatments can, however, only benefit patients if they are fully implemented in clinical care. Aim: This scoping review aimed to explore the literature for internet-based cognitive behavioural therapy in cardiovascular disease and for strategies to implement the intervention. Methods: We searched electronic databases, journals and internet sources to find original studies about internet-based cognitive behavioural therapy in cardiovascular disease, adhering to scoping methodology guidelines. After identifying 267 titles, we screened 40 abstracts and chose 11 full-text articles for full-text screening. The results sections in four articles were searched for outcomes that related to the effectiveness and implementation of internet-based cognitive behavioural therapy by directed qualitative content analysis using an implementation framework. Results: Three of the four articles fulfilling the inclusion criteria concerned internet-based cognitive behavioural therapy for treating mild to moderate depressive symptoms in cardiovascular disease, and none focused on insomnia. The studies showed evidence for the effectiveness of internet-based cognitive behavioural therapy, and/or described patient factors influencing clinical effectiveness. Our qualitative content analysis showed that many implementation aspects and stakeholder perspectives remain unexplored. Conclusions: Internet-based cognitive behavioural therapy promises to alleviate patient suffering in cardiovascular disease. There is, however, little research about internet-based cognitive behavioural therapy for cardiovascular disease, and about how this evidence-based intervention is implemented.